Identification of Novel Aryl Carboxamide Derivatives as Death-Associated Protein Kinase 1 (DAPK1) Inhibitors with Anti-Proliferative Activities: Design, Synthesis, In Vitro, and In Silico Biological Studies - Ahmed Elkamhawy; Sora Paik; Eslam M. H. Ali; Ahmed H. E. Hassan; So Jin Kang; Kyeong Lee; Eun Joo Roh (MDPI AG, 2022)
Death-associated protein kinase 1 (DAPK1) is a serine/threonine protein kinase involved in diverse fundamental cellular processes such as apoptosis and autophagy. DAPK1 isoform plays an essential role as a tumor suppressor and inhibitor of metastasis. Consequently, DAPK1 became a promising target protein for developing new anti-cancer agents. In this work, we present the rational design and complete synthetic routes of a novel series of eighteen aryl carboxamide derivatives as potential DAPK1 inhibitors. Using a custom panel of forty-five kinases, a single dose of 10 µM of the picolinamide derivative 4a was able to selectively inhibit DAPK1 kinase by 44.19%. Further investigations revealed the isonicotinamide derivative 4q as a promising DAPK1 inhibitory lead compound with an IC50 value of 1.09 µM. In an in vitro anticancer activity assay using a library of 60 cancer cell lines including blood, lung, colon, CNS, skin, ovary, renal, prostate, and breast cancers, four compounds (4d, 4e, 4o, and 4p) demonstrated high anti-proliferative activity with mean % GI ~70%. Furthermore, the most potent DAPK1 inhibitor (4q) exhibited remarkable activity against leukemia (K-562) and breast cancer (MDA-MB-468) with % GI of 72% and 75%, respectively.